2016
DOI: 10.1108/ejm-05-2015-0304
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the discounted attribute importance in two-sided messages

Abstract: Purpose-The purpose of this research is to test the importance of the discounting attribute in the two-sided communication from a retail salesperson as a boundary condition that eliminates the trade-off between trustworthiness and purchase intentions. Design/methodology/approach-The hypotheses are tested by three experimental studies in three different retail contexts. Two lab studies manipulate the importance of the attribute and the type of message: one-sided vs two-sided. A field study improves the external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…A one-sided persuasive message addresses only one-sided aspects or attributes (i.e., positive) of a person, product, or service. A two-sided message, on the other hand, is considered a kind of strong argument, where negative as well as positive information about a target or offering is strategically highlighted to mitigate the future surprise beforehand (see Dolnik, Case, & Williams, 2003; Pizzutti, Basso, & Albornoz, 2016). Research suggests that the relative effectiveness of a one-versus two-sided message differs as a function of initial attitude or prior perception (see Kao, 2011; O’Keefe, 1999; Sanaktekin & Sunar, 2008).…”
Section: Message Sidedness As Strategic Persuasive Message Tacticmentioning
confidence: 99%
“…A one-sided persuasive message addresses only one-sided aspects or attributes (i.e., positive) of a person, product, or service. A two-sided message, on the other hand, is considered a kind of strong argument, where negative as well as positive information about a target or offering is strategically highlighted to mitigate the future surprise beforehand (see Dolnik, Case, & Williams, 2003; Pizzutti, Basso, & Albornoz, 2016). Research suggests that the relative effectiveness of a one-versus two-sided message differs as a function of initial attitude or prior perception (see Kao, 2011; O’Keefe, 1999; Sanaktekin & Sunar, 2008).…”
Section: Message Sidedness As Strategic Persuasive Message Tacticmentioning
confidence: 99%
“…Because individuals in a promotion focus want the maximisation of positive results, a 2SM would make them feel more confident than a 1SM, increasing their positive responses. Similarly, it was found that it is possible to enhance trustworthiness through a 2SM, without mitigating the intentions of buying, by controlling the importance of the negative information provided (Pizzutti et al, 2016). These findings, confirming the importance of individuals’ confidence and trustworthiness, indicate that the individual’s self-confidence could have a moderating effect on the effectiveness of 2SMs.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the lack of clear explanations on the functioning of the effect of 2SMs on individuals’ responses, hampering their implementation by communication professionals. There have been several attempts to model and interpret the effect of 2SMs (Bohner et al, 2003; Chen, 2016; Cornelis et al, 2014, 2015; Eisend, 2007, 2008, 2010; Hastak & Park, 1990; Hunt et al, 1982; Kamins & Marks, 1987; Kao, 2011; Pizzutti et al, 2016; Trifts & Häubl, 2003). However, the diversity of the results, as highlighted by Eisend (2006), indicates the necessity of further research on moderating variables (Cornelis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The literature review identified a strand of theoretical development in the study of the effect of 2SMs, namely to establish the limits of the effect of 2SMs by analyzing how the effect occurs in different situations (e.g., online environments such as social networks and websites). In this regard, there have been several attempts to model and interpret the effect of 2SMs [3][4][5][6][7][8][9][14][15][16][17][18]. Nonetheless, the heterogeneity of the results, as pointed out by [9], still indicates the need for further investigation of substantive moderating variables [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the effect of 2SMs depends upon situational factors, such as: disclosure uniqueness, cognitive load and involvement [9], time pressure [14], and the importance of the negative attributes [18]. There is also evidence that the effect of the message may be moderated by some of its characteristics, such as regulatory congruence [15], issue ambivalence, and message arguments [16].…”
Section: Introductionmentioning
confidence: 99%